Consecutive Ligand‐Based Electron Transfer in New Molecular Copper‐Based Water Oxidation Catalysts. (30th July 2021) - Gil‐Sepulcre, Marcos; Garrido‐Barros, Pablo; Oldengott, Jan; Funes‐Ardoiz, Ignacio; Bofill, Roger; Sala, Xavier; Benet‐Buchholz, Jordi; Llobet, Antoni
Abstract: Water oxidation to dioxygen is one of the key reactions that need to be mastered for the design of practical devices based on water splitting with sunlight. In this context, water oxidation catalysts based on first‐row transition metal complexes are highly desirable due to their low cost and their synthetic versatility and tunability through rational ligand design. A new family of dianionic bpy‐amidate ligands of general formula H2 LN n − (LN is [2, 2′‐bipyridine]‐6, 6′‐dicarboxamide) substituted with phenyl or naphthyl redox non‐innocent moieties is described. A detailed electrochemical analysis of [(L4)Cu] 2− (L4=4, 4′‐(([2, 2′‐bipyridine]‐6, 6′‐dicarbonyl)bis(azanediyl))dibenzenesulfonate) at pH 11.6 shows the presence of a large electrocatalytic wave for water oxidation catalysis at an η=830 mV. Combined experimental and computational evidence, support an all ligand‐based process with redox events taking place at the aryl‐amide groups and at the hydroxido ligands. Abstract : A family of Cu‐based complexes bearing dianionic bpy‐amidate ligands have been prepared and characterized by spectroscopic and electrochemical techniques. The new complexes are capable of performing water oxidation catalysis at overpotentials between 557–830 mV pH 11.6. A detailed electrocatalytic study in combination with computational calculations revealed the all ligand‐based nature of the electron transfer processes involved in the catalytic cycle.